Description of two new species in long-horned crane fly subgenus Tipula (Sivatipula) (Diptera: Tipulidae) from China - Men, Qiu-Lei; Tang, Li; Wu, Li-Mei; Ji, Zhi-Xin; Li, Cong-Hu (Zootaxa, 2018)
Two new species of subgenus Tipula (Sivatipula) Alexander, 1964, T. (S.) multidentata sp. nov. (southern China: Guizhou) and T. (S.) tergatruncata sp. nov. (southern China: Chongqing) are described and illustrated.